Pseudomonas aeruginosa GidA modulates the expression of catalases at the posttranscriptional level and plays a role in virulence - Srimahaeak, Thanyaporn; Thongdee, Narumon; Chittrakanwong, Jurairat; Atichartpongkul, Sopapan; Jaroensuk, Juthamas; Phatinuwat, Kamonwan; Phaonakrop, Narumon; Jaresitthikunchai, Janthima; Roytrakul, Sittiruk; Mongkolsuk, Skorn; Fuangthong, Mayuree (Frontiers in Microbiology, 2023)
P. aeruginosa gidA, which encodes a putative tRNA-modifying enzyme, is associated with a variety of virulence phenotypes. Here, we demonstrated that P. aeruginosa gidA is responsible for the modifications of uridine in tRNAs in vivo. Loss of gidA was found to have no impact on the mRNA levels of katA and katB, but it decreased KatA and KatB protein levels, resulting in decreased total catalase activity and a hydrogen peroxide-sensitive phenotype. Furthermore, gidA was found to affect flagella-mediated motility and biofilm formation; and it was required for the full virulence of P. aeruginosa in both Caenorhabditis elegans and macrophage models. Together, these observations reveal the posttranscriptional impact of gidA on the oxidative stress response, highlight the complexity of catalase gene expression regulation, and further support the involvement of gidA in the virulence of P. aeruginosa.